A controlled synthesis of γ-MnOOH nanorods via a facile hydrothermal method for high-performance Li-ion batteries. Issue 12 (8th March 2021) - Zhang, Yuting; Dong, Xuelu; Li, Haibo; Cui, Chuansheng; Fu, Chonggang; Zeng, Suyuan; Wang, Lei
Abstract : A hydrothermal reduction route was used for the controlled production of MnOOH nanostructures. The formed γ-MnOOH nanorods can be used as one of the high performance anodes for the preparation of lithium ion batteries. Abstract : In this study, a hydrothermal reduction route was applied for the controlled production of MnOOH nanohydrangeas and MnOOH nanorods. The structure and morphology of the formed products were characterized. Both MnOOH nanohydrangeas and nanorods were utilized as active anodes for Li-ion batteries. Galvanostatic charge–discharge, cyclic voltammogram, rate performance, and electrochemical impedance were analyzed to compare the lithium ion energy storage performances of the two MnOOH nanostructures. The results indicate that γ-MnOOH nanorods possess enhanced cycle and rate capacity compared with the γ-MnOOH nanohydrangeas. At a current density of 200 mA g −1, a specific capacity of 965 mA h g −1 is obtained for the formed γ-MnOOH nanorods after 200 cycles, while the reversible capacity of MnOOH nanohydrangeas is 380 mA h g −1, which suggests that the morphology variation of the as-prepared MnOOH nanostructures can influence the electrochemical properties. γ-MnOOH nanorods synthesized by this method present a prospective application for lithium ion batteries.